2014
DOI: 10.1016/j.shaw.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Thai Version of a Work-related Quality of Life Scale in the Nursing Profession

Abstract: BackgroundCurrently available questionnaires for evaluating the quality of worklife do not fully examine every factor related to worklife in all cultures. A tool in Thai is therefore needed for the direct evaluation of the quality of worklife. Our aim was to translate the Work-related Quality of Life Scale-2 (WRQLS-2) into Thai, to assess the validity and reliability of the Thai-translated version, and to examine the tool's accuracy vis-à-vis nursing in Thailand.MethodsThis was a descriptive correlation study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…[121920] We observed that the “item 2” (“I feel able to voice opinions and influence changes in my area of work”) in CAW domain was weak due to a high “alpha if item deleted.” Removal of this item increased the reliability of the CAW sub-scale. Item two has been suggested for removal by previous studies also, although they used other analytical tools.…”
Section: Discussionmentioning
confidence: 99%
“…[121920] We observed that the “item 2” (“I feel able to voice opinions and influence changes in my area of work”) in CAW domain was weak due to a high “alpha if item deleted.” Removal of this item increased the reliability of the CAW sub-scale. Item two has been suggested for removal by previous studies also, although they used other analytical tools.…”
Section: Discussionmentioning
confidence: 99%
“…The socio-demographic variables included age, sex, education, and monthly income and the work characteristics included type of hospital, job position, length of current work, work hours, shift work, and perception of urgent task were established.The quality of work life factors included general well-being and employee engagement was measured applying the Thai-Work-Related Quality of Life Scale (WRQLS). 10 Items of WRQLS were scored regarding feelings oropinions on a five-point Likert-type scale, ranging from 1 = never to 5 = very high. The Cronbach's α of general well -being and employee engagement scale was 0.82 and 0.84, respectively.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Previous validation of the WRQoL scale was conducted by several scholars (e.g. Chaiea 2014; Sirisawasd et al 2014). Job performance was measured using six items adapted from the 'Role-Based Performance Scale' (Welbourne et al 1998), which was validated by Walumbwa et al (2008).…”
Section: Measurement Instrumentmentioning
confidence: 99%